FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENYULUH PERTANIAN DAN DAMPAKNYA TERHADAP PRODUKSI PADI PETANI DI KABUPATEN SIAK - Elka Roza; Rosnita Rosnita; Fajar Restuhadi (PEKBIS, 2018)
Performance of agricultural extension workers is the result of the work of extensionworkers in carrying out the tasks assigned to him. The aim of this research is toanalyze how big the influence of extension characteristic, extension role, extensioncompetence, and extension motivation to agricultural extension performance and toanalyze the impact of agricultural extension performance on paddy production inSiak Regency. Data analysis method used in this research is multiple regressionanalysis. The results of analysis indicate that the characteristics of extension, therole of extension, extension and extension motivation have influenced the extensionperformance level in Siak Regency. This indicates the agricultural extension hasbeen running well and functioning as expected. As well as the influence ofagricultural extension performance level on rice production shows the level ofperformance gives influence to paddy production seen from the implementation ofextension, evaluation and reporting. Meanwhile, the level of performance in thepreparation of extension has not affected rice production.